Histological pattern of tumor inflammation and stromal density correlate with patient demographics and immuno-oncologic transcriptional profile in oral squamous cell carcinoma - Theofilou, Vasileios Ionas; Ghita, Ioana; Elnaggar, Manar; Chaisuparat, Risa; Papadimitriou, John C.; Bentzen, Soren M.; Dyalram, Donita; Lubek, Joshua E.; Ord, Robert A.; Younis, Rania H. (Frontiers in Oral Health, 2024)
Introduction: Oral squamous cell carcinoma (OSCC) is the most prevalent oral malignancy, with emerging interest in the characterization of its tumor microenvironment. Herein, we present a comprehensive histological analysis of OSCC stromal density and inflammation and their relationship with patient demographics, clinicopathologic features and immuno-oncologic signatures. Materials-Methods: Eighty-seven completely excised OSCC tissues were prospectively collected and scored for histopathologic inflammatory subtypes [HIS] - inflamed (INF), immune-excluded (IE) and immune-desert (ID)-, peritumoral stromal inflammation (PTSI), and peritumoral stromal fibrosis (PTSF). Scoring of inflammation was complemented by Semaphorin 4D immunohistochemistry. NanoString differential gene expression (DGE) analysis was conducted for eight OSCC cases representative of the inflammatory and stromal subtypes and the demographic groups. Results: PTSF correlated with male gender (p=0.0043), smoking (p=0.0455), alcohol consumption (p=0.0044), increased tumor size (p=0.0054), and advanced stage (p=0.002). On the contrary, PTSI occurred predominantly in females (p=0.0105), non-drinkers (p=0.0329), and small tumors (p=0.0044). Transcriptionally, decreased cytokine signaling, and oncogenic pathway activation were observed in HIS-IE. Smokers and males displayed decreased global immune-cell levels and myeloid-cell predominance. Conclusion: Our work describes OSCC stromal and inflammatory phenotypes in correlation with distinct patient groups and DGE, highlighting the translational potential of characterizing the tumor microenvironment for optimal patient stratification.